Reputation risk management on the discourse of Samarco corporate reports - Oliveira, José Alex Nobrega de; Cintra, Yara Consuelo (Revista de Contabilidade e Organizações, 2019)
The objective of this research is to investigate the influence of reputation risk management (RRM) on the disclosure of corporate reports, especially sustainability reports. The study analysed reports of Samarco - mining company responsible for the Fundão dam in Mariana, Minas Gerais, Brazil, object of the accident occurred in November 2015. The period comprised 2010 to 2016, the latter covering the disaster and its social and environmental impacts. The content analysis of the reports suggests the use of social and environmental reports as an RRM tool by analyzing selected reputation elements and applying an image restoration typology. The findings contribute to the understanding of the determinants of socio-environmental disclosure, broadening the spectrum of legitimacy theory, adding the reputation component and risk management to reputation.